2019
DOI: 10.14744/bej.2019.39306
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Optic Coherence Tomography Changes Before and After Phacoemulsification in Primary Open Angle Glaucoma

Abstract: The goal of this study was to compare measurements of values such as the anterior chamber angle (ACA), thickness of the iris, thickness of the cornea, and the angle-opening distance (AOD) of eyes with primary open-angle glaucoma before and after undergoing phacoemulsification with intraocular lens implantation using anterior segment optical coherence tomography (AS-OCT). Methods: The data of 49 eyes of 39 glaucoma patients who presented at the Cataract and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…With the rapid development of medical diagnostics, the early screening of glaucoma relies on the measurement of retinal nerve fiber layer thickness by optical tomography (OCT) combined with intraocular pressure detection. Numerous studies have shown that the use of optical tomography scanners to detect the thickness of the retinal fiber layer can only be effective when the onset of glaucoma reaches a certain point [ 41 , 42 , 43 , 44 , 45 ] such that the retinal nerve fiber layer has been damaged.…”
Section: Introduction Of Optic Nerve Injury Ophthalmopathy and Animal...mentioning
confidence: 99%
“…With the rapid development of medical diagnostics, the early screening of glaucoma relies on the measurement of retinal nerve fiber layer thickness by optical tomography (OCT) combined with intraocular pressure detection. Numerous studies have shown that the use of optical tomography scanners to detect the thickness of the retinal fiber layer can only be effective when the onset of glaucoma reaches a certain point [ 41 , 42 , 43 , 44 , 45 ] such that the retinal nerve fiber layer has been damaged.…”
Section: Introduction Of Optic Nerve Injury Ophthalmopathy and Animal...mentioning
confidence: 99%